Evaluation of Heavy Metal Adsorption Efficiency of Biochars Derived from Agricultural Waste - Velyana Georgieva; Lenia Gonsalvesh; Sonia Mileva; Mariyana Hamanova; Hyusein Yemendzhiev (Biomass, 2025)
This study investigates the potential of biochars derived from agricultural waste biomass for the removal of heavy metal ions from aqueous solutions. Biochars were produced via slow pyrolysis at 793 K using almond shells (AS), walnut shells (WS), pistachio shells (PS), and rice husks (RH) as feedstocks. The physicochemical properties and adsorption performance of the resulting materials were evaluated with respect to Cd(II), Mn(II), Co(II), Ni(II), Zn(II), total Iron (Fetot), total Arsenic (Astot), and total Chromium (Crtot) in model solutions. Surface morphology, porosity, and surface chemistry of the biochars were characterized by scanning electron microscopy (SEM), nitrogen adsorption at 77 K (for specific surface area and pore structure), Fourier-transform infrared spectroscopy (FTIR), and determination of the point of zero charge (pHpzc). Based on their textural properties, biochars derived from WS, PS, and AS were classified as predominantly microporous, while RH-derived biochar exhibited mesoporous characteristics. The highest Brunauer–Emmett–Teller (SBET) surface area was recorded for PS biochar, while RH biochar showed the lowest. The pistachio shell biochar exhibited the highest specific surface area (440 m2/g), while the rice husk biochar was predominantly mesoporous. Batch adsorption experiments were conducted at 25 °C, with an adsorbent dose of 3 g/L and a contact time of 24 h. The experiments in multicomponent systems revealed removal efficiencies exceeding 87% for all tested metals, with maximum values reaching 99.9% for Cd(II) and 97.5% for Fetot. The study highlights strong correlations between physicochemical properties and sorption performance, demonstrating the suitability of these biochars as low-cost sorbents for complex water treatment applications.